Social egg freezing under public health perspective: Just a medical reality or a women’s right? An ethical case analysis - Ana Borovecki; Pamela Tozzo; Nicoletta Cerri; Luciana Caenazzo (Journal of Public Health Research, 2018)
In recent years, a social trend toward delaying childbearing has been observed in women of reproductive age. A novel technomedical innovation was commercialized for non-medical reasons to healthy, ostensibly fertile women, who wished to postpone motherhood for various reasons such as educational or career demands, or because they had not yet found a partner. As a consequence, these women may be affected by age-related infertility when they decide to conceive, and fertility preservation techniques can be obtained through the so-called social egg freezing. This paper examines, from an ethical point of view, the impact of social egg freezing under some aspects that can involve policy making and resources allocation in public health. Due to the increasing demand for this procedure, some debated issues regard if it is reasonable to include social egg freezing in Public Healthcare System and consequently how to manage the storage of cryopreserved oocytes also from individual donors, how to support these egg banks and how to face, in the future, with the possibility that egg freezing will play a role in enabling childbearing for gays, lesbians, and unmarried persons. Social freezing may be advertised to harmonise gender differences, but we wonder if it is the proper solution to the problem or if it could also create further challenges. An ethical argumentation on these topics should address some questions that will be discussed.